2022
DOI: 10.21203/rs.3.rs-1918209/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Extraction of Avocado Peel Oil Using a Soxhlet Extractor and Investigation of Its Physicochemical Properties

Abstract: This study investigates the extraction of avocado peel oil from avocado peel using a soxhlet extractor at different extraction times, temperatures, and solvent to avocado peel ratios using hexane solvent. The time for extraction ranges from 2 to 5 h, the extraction temperature ranges from 60 to 70°C at a temperature deviation of ± 2°C, and the hexane to avocado peel ratio ranges from 4 to 5 ml/g. Thus, the study reveals that the maximum amount of 29.93% w/w avocado peel oil was extracted at 3 h of extraction, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
0
1

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 18 publications
2
0
1
Order By: Relevance
“…The values for specific gravity of APO in this study ranged from 0.84 ± 0.0 to 0.9 ± 0.0 with APSB having the highest specific gravity. This is same as the value of specific gravity reported by [21]. The specific gravities of AO by Ogbaugu et al, 2020 was reported to be 0.86.…”
Section: Specific Gravitysupporting
confidence: 88%
See 2 more Smart Citations
“…The values for specific gravity of APO in this study ranged from 0.84 ± 0.0 to 0.9 ± 0.0 with APSB having the highest specific gravity. This is same as the value of specific gravity reported by [21]. The specific gravities of AO by Ogbaugu et al, 2020 was reported to be 0.86.…”
Section: Specific Gravitysupporting
confidence: 88%
“…This value is close to the value of avocado oil (0.91 ± 0.01) reported by [20]. Generally, the values are higher as compared to the 0.90 reported by [21]. This could be due to the geographical factors affecting the growth and properties of the avocado pears.…”
Section: Densitysupporting
confidence: 81%
See 1 more Smart Citation